ChemInform Abstract: Tailoring the Catalytic Properties of Metal Nanoparticles via Support Interactions. Issue 47 (3rd November 2016) - Ahmadi, M.; Mistry, H.; Roldan Cuenya, B.
Abstract: Review: 170 refs.